Construction du sujet-femme et imaginaire dissident : Largo desolato de Václav Havel - Deret, Anne (Université du Québec à Montréal, 1997)
Keywords: 1900-1999; 1980-1989; IREF; discipline; europe; mémoires/thèses; périodes historiques; régions géographiques; république tchèque; science politique; théâtre

Feminisms: An anthology of literary theory and criticism - Warhol, Robyn R.; Price Herndl, Diane (Rutgers University Press, 1997)
This volume brings together 58 previously published essays on 19th and 20th century British and North American texts that were written from the mid-1970s to 1990 by feminist literary critics. These essays cover a variety of critical perspectives, including Anglo-American, French, Marxist, structuralist, new historicist, and psychoanalytic. The 13 sections of the book cover various issues in feminist criticism: institutions, methodologies, canon, tradition, body, desire, reading, discourse, ethnicity, history, class, men, and autobiography. Each section includes essays addressing the intersections of feminist concern with questions of class, race, sexual preference, and nationality. Contributors include Barbara Christian, Sandra M. Gilbert, Susan Gubar, Helene Cixous, and Elaine Showalter
Keywords: 1900-1999; amériques; anthologie; arts; discipline; europe; fem1000; histoire et politique; littérature; premier cycle; périodes historiques; royaume-uni; régions géographiques; thématiques; théories féministes; états-unis; études littéraires